Execution by Styrax in ancient Thasos - Agelarakis, Anagnostis P., 1956- (Access archaeology., 2019)
Sharing in the objectives of an ongoing archaeo-anthropological endeavour, aiming to better decipher and elucidate facets of the human condition while carrying out funerary archaeological research of Hellenistic to Roman periods family graves at the extensive ancient necropolis of Thasos, the most northern Aegean island, this essay addresses a case of unique forensic / bioarchaeological interest involving an older male individual, a member of one of the clusters of burials, who had been placed as a single interment in a most conspicuous limestone cyst grave of the Hellenistic period.